Grandma Moses - Biracree, Tom, 1947- (New York : Chelsea House Publishers, 1989)
A biography of the American primitive painter who, at the age of seventy-six, without ever having had an art lesson, began painting realistic scenes of rural life which were critically acclaimed and made her famous.
Includes index.
Bibliography: p. 104.
Keywords: Moses, -- Grandma, -- 1860-1961 -- Juvenile literature; Moses, -- Grandma, -- 1860-1961.; Painters -- United States -- Biography -- Juvenile literature; Artists